SERVICE PERFORMANCE IMPROVEMENT DURING PANDEMIC COVID 19 USING INTEGRATED SERVQUAL AND SIX SIGMA: TELECOMMUNICATION AND INFORMATION INDUSTRY CASE APPLICATION - Sulton Nur Hakim; Alfatah Kalijaga; Sri Indrawati (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2020)
The increase in users of the Wifi.id Corner internet service is not directly proportional to the service satisfaction obtained by the Wi-Fi.id Corner service. In fact, many Wifi.id Corner customers complain and still complain about the quality of Wifi.id Corner services ranging from unstable network problems, slow speeds, to problems with the location. An analysis is needed to find out these problems. The purpose of this study is to assess the level of customer satisfaction with service quality and determine the priority attributes in improving service Wi-Fi.id Corner. The method used in this research is Service Quality (SERVQUAL) and Six Sigma. From the research results, it is found that the services provided by PT X have not fulfilled the wishes of its customers optimally, this can be shown by the high gap value and low sigma value. The following are three attributes that are an important concern for the company because they have the lowest sigma value: environmental cleanliness Wifi.id Corner with gap and sigma values of -1.30 and 1.88, internet speed stability R2 with gap and sigma values Of -1, 27 and 1.85, it is rare for interference in accessing the internet R4 with gap and sigma values of -1.23 and 1.85.